Avaliação do comportamento mecânico de tubos de concreto reforçado com fibras de aço - Jesus, Paula Andreatti De [UNESP] (2025)
The purpose of this study was perform an experimental evaluation of the mechanical behavior of concrete pipes reinforced with steel fibers when subjected to the diametral compression test, as required by NBR 8890:2020. Pipes of the socket and spigot type were produced, with nominal diameters of 400 mm, 500 mm, and 600 mm for resistance classes PA1 and PA2, all with a length of 1500 mm and reinforced with 30 kg/m³ of Dramix 3D 65/35 BG steel fibers. The pipes were equipped with LVDTs and subjected to the diametral compression test. Analysis of the results, through the construction of load versus time and load versus diametral displacement curves, allowed for the conclusion that a consumption of 30 kg/m³ of steel fibers is sufficient to meet the resistance criteria of the standard. It was also observed that the smaller diameter pipes and lower strength class exhibited more favorable results regarding fiber consumption. Additionally, the findings indicated that the spigot region is the most critical section of the conduit, as cracks initiated in this area and displacements were greater compared to the socket.